RISING STUDENT’S ACADEMIC HONESTY: THE IMPLEMENTATION OF CLASSROOM DEVELOPMENTAL BIBLIOTHERAPY (CDB) IN BAHASA INDONESIA LEARNING AT MADRASAH IBTIDAIYAH - Siti Khorriyatul Khotimah (JPDI (Jurnal Pendidikan Dasar Indonesia), 2017)
The aims of this research are to find out: (1) the implementation of classrooom developmental bibliotherapy (CDB) in Bahasa Indonesia learning process to improve student’s academic honesty, and (2) the result of the implementation of CDB in Bahasa Indonesia learning to improve student’s academic honesty. This is a classroom action research. The subjects are 28 students from 5th grade of MI (Madrasah Ibtidaiyah) Cahaya. This research has 3 cycles with 3 to 4 sessions in every cycle. In every session, the learning process are integrated CDB’s stage into Bahasa Indonesia learning process in competencies: reading, writing, and speaking. The qualitative and quantitative data are collected with several technics: observation, interview, students self report and students journals analizes. The process of data analysis are: data reduction, data display, and an overview of conclusions / verification. The data analizes is explained as findings and reflections in every cycle that will be follow up to the next cycle or stop the action. The result are: (1) the implemention of CDB in Bahasa Indonesia learning are success especially in playing drama, and (2) the improvement of student’s academic honesty is known from by the number of honest student increase to 96%, and the students show some behavior to maintain their academic honesty.